2017
DOI: 10.1021/acscatal.7b01166
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental-Theoretical Study of the LigW-Catalyzed Decarboxylation of 5-Carboxyvanillate in the Metabolic Pathway for Lignin Degradation

Abstract: Although it is a member of the amidohydrolase superfamily, LigW catalyzes the nonoxidative decarboxylation of 5-carboxyvanillate to form vanillate in the metabolic pathway for bacterial lignin degradation. We now show that membrane inlet mass spectrometry (MIMS) can be used to measure transient CO2 concentrations in real time, thereby permitting us to establish that C−C bond cleavage proceeds to give CO2 rather than HCO3 − as the initial product in the LigW-catalyzed reaction. Thus, incubation of LigW at pH 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 32 publications
9
54
0
Order By: Relevance
“…Although it has been demonstrated that entropy only has a small effect on the energies of the chemical step of enzyme reactions (Senn et al, 2005 , 2009 ; Hu and Zhang, 2006 ; Lonsdale et al, 2012 ; Kazemi et al, 2016 ; Mulholland, 2016 ), its contribution must be considered in the case of a release of a gas molecule, which is relevant for the CO 2 release considered in the current study. In line with previous studies (Blomberg and Siegbahn, 2012 ; Lind and Himo, 2014 ; Sheng et al, 2015 , 2017 ), the entropy gain can be estimated as the translational entropy for the gas molecule (calculated to 11.3 kcal/mol), which is added at all steps after the transition state of CO 2 formation. Finally, the energies of the transition states corresponding to Int2 → Int3a , Int4b → Int5 , and Int6 → Int7 steps were computed to be slightly lower than one or both of the connecting intermediates.…”
Section: Computational Detailssupporting
confidence: 57%
“…Although it has been demonstrated that entropy only has a small effect on the energies of the chemical step of enzyme reactions (Senn et al, 2005 , 2009 ; Hu and Zhang, 2006 ; Lonsdale et al, 2012 ; Kazemi et al, 2016 ; Mulholland, 2016 ), its contribution must be considered in the case of a release of a gas molecule, which is relevant for the CO 2 release considered in the current study. In line with previous studies (Blomberg and Siegbahn, 2012 ; Lind and Himo, 2014 ; Sheng et al, 2015 , 2017 ), the entropy gain can be estimated as the translational entropy for the gas molecule (calculated to 11.3 kcal/mol), which is added at all steps after the transition state of CO 2 formation. Finally, the energies of the transition states corresponding to Int2 → Int3a , Int4b → Int5 , and Int6 → Int7 steps were computed to be slightly lower than one or both of the connecting intermediates.…”
Section: Computational Detailssupporting
confidence: 57%
“…In both decarboxylation pathways, it is clear that the enzyme must generate an adjacent electron sink (such as the ketone carbonyl C4 since the formation of the new carbon–hydrogen bond) to stabilize the incipient carbanion at C5 prior to decarboxylation. This mechanism corresponds to that explored in the recent combined experimental and theoretical work (Sheng et al, 2017 ) where the membrane inlet mass spectrometry (MIMS) based assay is applied to study the LigW mechanism. The above-mentioned MIMS-based strategy (Sheng et al, 2017 ) was able to establish CO 2 and not as reaction product.…”
Section: Resultsmentioning
confidence: 58%
“…This mechanism corresponds to that explored in the recent combined experimental and theoretical work (Sheng et al, 2017 ) where the membrane inlet mass spectrometry (MIMS) based assay is applied to study the LigW mechanism. The above-mentioned MIMS-based strategy (Sheng et al, 2017 ) was able to establish CO 2 and not as reaction product. We have considered also the path for the bicarbonate release but our calculated PESs with the three models used give very high energetic barriers (see Table S1 ) that are not compatible with the enzymatic kinetics.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations